Symposium 4: The Global Institution, the Homely, and the Overwhelming: (per)forming three MOOC spaces - Knox, Jeremy (Proceedings of the International Conference on Networked Learning, 2014)
While being a relatively recent phenomenon in higher education, the Massive Open Online Course (MOOC) has attracted significant media attention for offering free participation and attracting unprecedented enrolment numbers, often in the tens of thousands. Coursera, and edX have emerged as the principle MOOC platform providers, entering into partnerships with a significant number of higher education institutions, mostly located in the US, and promoting themselves as global organisations that disrupt geographical barriers to higher education. MOOCs are often marketed in terms of accessibility and egalitarianism by providing unproblematic admittance to university education. However, the space of the MOOC is significantly under-theorised, and like much of education in general it is often ‘left unexamined as simply a different context, container or backcloth for curriculum and pedagogy’ (Fenwick et al. 2011, p220). This paper draws from spatial theory and the mobilities turn to consider what kinds of spaces are being (per)formed in the emerging domains of the MOOC. It will describe three different enactments of space: the ‘global institution’; the ‘homely’; and the ‘overwhelming’, involving from the promotion of particular MOOC platforms and the activities of two specific courses. The paper will draw upon visual, discursive and technological elements in these examples to consider how notions of space can be articulated and enacted through promotion, participation and digital intervention. ‘Global-institutional’ space concerns the ways that MOOC platforms advance an arrangement that maintains the traditional structure of the institution alongside claiming a global reach. ‘Homely’ space involves promotion of a local community building as the locus of course activity during a specific MOOC, privileging a central and authentic site of scholarly occupation. ‘Overwhelming’ space concerns participant responses to an unconventional MOOC utilising distributed social media spaces and encouraging student-created content. Student responses from this course will be used to enact the space of the MOOC, not as the passive scenery external to educational activity, but rather as an active and relational process which emerges within; through relations with the subjects, activities, technologies and objects of online education.